MARKETING IN SOCIAL NETWORKS: HOW BRANDS BUILD RELATIONSHIPS WITH CLIENTS (Web of Technology: Multidimensional Research Journal, 2025)
Our article is devoted to the analysis of social media marketing, with an emphasis on how brands build relationships with customers through various platforms. In the article, we consider key tools and methods of interaction with the audience, including content marketing, targeted advertising, and a strategy for interacting with subscribers.